2022
DOI: 10.1016/j.jadohealth.2022.01.003
|View full text |Cite
|
Sign up to set email alerts
|

Parents’ Willingness to Vaccinate Their Children With COVID-19 Vaccine: Results of a Survey in Italy

Abstract: Purpose This cross-sectional study was conducted to assess the parents’ willingness to vaccinate their children with COVID-19 vaccine and related determinants with specific attention to willingness for adolescents as compared to younger children. Methods Data were collected through a confidential online questionnaire. Results A total of 607 parents agreed to participate. More than two-thirds of the parents had a good knowledge about the modes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
29
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 38 publications
7
29
3
Order By: Relevance
“…Aside from the high willingness to get vaccinated among the students in our study, 78.1% of parents in the same area (Chiang Mai’s urban district) agreed that their children should be vaccinated ( Figure S1C ). These findings were consistent with previous research findings relative to either adolescents or parents [ 45 , 46 ] ( Figure S1C ) [ 20 ]. Immunization may not be as frightening for adolescents as it is for younger children, whose parents were less likely to allow them to be vaccinated [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…Aside from the high willingness to get vaccinated among the students in our study, 78.1% of parents in the same area (Chiang Mai’s urban district) agreed that their children should be vaccinated ( Figure S1C ). These findings were consistent with previous research findings relative to either adolescents or parents [ 45 , 46 ] ( Figure S1C ) [ 20 ]. Immunization may not be as frightening for adolescents as it is for younger children, whose parents were less likely to allow them to be vaccinated [ 47 ].…”
Section: Discussionsupporting
confidence: 93%
“…According to our results, the percentage of Greek parents who intended to vaccinate their children from 5 to 17 years of age was 54.7%, while 92.6% of pediatricians recommended pediatric vaccination against COVID-19. These findings are consistent with global and country-specific estimates during the same period [ 13 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Discussionsupporting
confidence: 90%
“…Thus, in this current scenario, it seems crucial to investigate willingness and hesitancy related to pediatric COVID‐19 vaccine, in order to understand the possible reasons for non‐vaccination, and investigate those factors that may affect vaccine acceptability. In Italy, the willingness to accept COVID‐19 vaccination in the general population ranged from 65% to 84%, whereas the intention to get their children vaccinated is between 60% and 74.5% in parents of children aged 12–18 years (di Giuseppe et al, 2022 ; Montalti et al, 2021 ) and 65.5% in parents of 5–11 aged children (di Giuseppe et al, 2022 ). However, it is worth mentioning that such willingness rates were collected before vaccination for children under 12 was possible in Italy.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding parental roles (mother vs. father), results are mixed: some studies highlighted that mothers show greater levels of vaccine hesitancy compared to fathers (Goldman et al, 2020 ; Montalti et al, 2021 ; Xu et al, 2021 ; Zhang et al, 2021 ), whereas other studies found the opposite (Russo et al, 2021 ). As for children's age, parents who show a greater vaccine hesitancy have generally younger children (di Giuseppe et al, 2022 ; Goldman et al, 2020 ; Montalti et al, 2021 ; Musa et al, 2021 ; Russo et al, 2021 ; Zhang et al, 2021 ) or children with chronic illnesses (Musa et al, 2021 ). Moreover, individual differences in parents' beliefs, attitudes, and personality characteristics might also affect the attitude toward vaccination.…”
Section: Introductionmentioning
confidence: 99%